Cote d'Ivoire : Selected Issues. (IMF Staff Country Reports; Country Report, 2016)
This paper examines Cote d'Ivoire's growth experience and argues that the development of a manufacturing export sector, lower income inequality, and prudent fiscal policy would strengthen the sustainability of growth. This paper aims to draw lessons for Cote d'Ivoire based on experience of other comparable countries that are now emerging market economies. The financial sector could trigger a shock to the economy or reinforce impact on the real sector of nonfinancial shocks. The current economic conditions in Cote d'Ivoire offer a favorable opportunity to resolve the financial status of public entities facing difficulties and for banks to raise their capital buffers to absorb a possible rise of nonperforming loans in event of a growth shock.